CONTRACT LAW TRAINING FOR BUSINESS STUDENTS - Suwinto Johan; Alicya Pingkan Elizabeth Watung; Fitri Amalia Rahman; Selly Angelina (Rural Development For Economic Resilience (RUDENCE), 2023)
ABSTRACT The agreement contains a contract that ensures equity and justice for both parties, and no party should be harmed. A contract is a written agreement that governs a business activity. This training is presented to students in order to learn more about a business contract agreement. Webinars will be used to deliver the training. Webinars are online training seminars that use video. The implementation technique includes training or seminars as well as questions and answers about the topic of discussion. Following a webinar, students understand the relevance of contractual agreements. A business student will learn more than just the theory of contract law. The sharing of experience and expertise from business professionals will increase the general public's and business students' knowledge of contract law. Participants in this webinar learned about the importance of a business agreement after attending this event. ABSTRAK Perjanjian merupakan kontrak yang menjamin pemerataan dan keadilan bagi kedua belah pihak, dan tidak boleh ada pihak yang dirugikan. Kontrak adalah perjanjian tertulis yang mengatur kegiatan bisnis. Pelatihan ini diberikan kepada mahasiswa untuk lebih mengenal perjanjian kontrak bisnis. Webinar akan digunakan untuk menyampaikan pelatihan. Webinar adalah seminar pelatihan online yang menggunakan video. Teknik pelaksanaannya meliputi pelatihan atau seminar serta tanya jawab seputar topik pembahasan. Mengikuti webinar, siswa memahami relevansi perjanjian kontrak. Mahasiswa bisnis akan belajar lebih dari sekedar teori hukum kontrak. Berbagi pengalaman dan keahlian dari para profesional bisnis akan meningkatkan pengetahuan masyarakat umum dan mahasiswa bisnis tentang hukum kontrak. Peserta webinar ini mengetahui mengenai pentingnya sebuah perjanjian bisnis setelah mengikuti acara ini.